On the status of Hypena helenae Berio, 1972 (Lepidoptera, Erebidae) - Karisch, Timm; Kramp, Katja (Zootaxa, 2022)
The authors present the results of morphological, anatomic and genetic studies on Hypena helenae Berio, 1972. They revealed the synonymy of this species with Hypena commixtalis Zeller, 1852 (Hypena helenae Berio, 1972 syn. nov.).